Crowdsourcing Platforms as Devices to Activate Subjectivities - Risi, Elisabetta; Briziarelli, Marco; Armano, Emiliana (PARTECIPAZIONE E CONFLITTO, 2019)
Our contribution examines the phenomenon of crowdsourcing platforms and its shaping of workers’ subjectivities. We focus on the process of soliciting unpaid services from (often precarious) knowledge workers operating through digital platforms, whose hope is to increase their employability chances. The paper presents and discusses the results of a qualitative research conducted during 2017-18 period, consisting of in-depth interviews with freelancers digital designers, who work in the Milan area, Italy. The findings contribute to enrich the conceptualization of ’free work’ by acknowledging the process of platforms mediation and their distinctive way of activating subjects. We also claim that while the term ’crowd’ highlights the collective and participatory dimension of ’crowdsourced’ projects, it obscures the fundamental mechanisms in determining their success: competition among participants, as well as the logic behind the so-called jackpot economy.